Corporate governance and earnings management in Chinese listed companies - Xiao, Ke (2019)
This study will attempt to identify which aspects of corporate governance affect the levels of earnings management in A-shares companies listed in China. It will use the Chinese Stock Market & Accounting Research (CSMAR) website to obtain data on 1262 companies over 5 years, from 2013 to 2017, for a total of 6310 observations. The study will use these observations in a modified Jones model to evaluate earnings management. It will then perform a regression to obtain results for each of its variables of corporate governance, showing how any of them relate to earnings management in China, then discussing the implications of these results in detail. It will show that the size of the board of supervisors and the largest shareholder’s percentage are both negatively correlated with discretionary accruals, which is used to indicate earnings management. It will also show that the other variables (CEO duality, managerial ownership, the board size, and board independence) all have no relationship with earnings management in the sample for this study. The study concludes that earnings manipulation is more common in China than previously believed, and that research into this area is still lacking depth and this study should be expanded upon in the future to increase understanding of the earnings management which happens in China and other East Asian countries. It finishes by acknowledging the limitations of its method and how research in the future could improve on it.